Novel approach towards colour imaging using a scanning laser ophthalmoscope. Issue 4 (1st April 1998) - Manivannan, A; Kirkpatrick, J N P; Sharp, P F; Forrester, J V
Abstract : AIMS: Conventional fundus imaging using a fundus camera produces colour fundus pictures. The scanning laser ophthalmoscope (SLO) has the advantages of lower levels of light exposure, improved contrast, and direct digital imaging but until now has produced monochromatic images as a laser of single wavelength is used. True representation of the fundus is possible by combining images taken using blue, green, and red lasers. METHODS: A custom built SLO was used to capture blue, green, and red fundus images from suitable volunteers and patients with fundus disease. Images were corrected for eye movement and combined to form a colour image. Colour fundus photographs were taken using a fundus camera for comparison with the SLO image. RESULTS: The background fundus and retinal vasculature had similar appearances with the two imaging modalities. Internal limiting membrane reflections were prominent with the SLO. Identification of new vessels in the diabetic fundus was easier with the SLO than the colour fundus photographs. CONCLUSION: A colour SLO offers all the advantages of the present monochromatic imaging system with the added advantage of true colour representation of the fundus.